PEMODELAN BRACING KABEL SERAT KARBON BERDASARKAN VALIDASI LOAD DRIFT EKSPERIMEN - Yasa, P Adi; Bhisama, Ida Bagus Prastha; Prayoga, Made Hendra (Jurnal Ilmiah Teknik Sipil, 2023)
The application of bracing is one of the most popular reinforcement methods applied to improve the lateral resistance of a building. Steel bracing is one of the most common and has good effectiveness in increasing lateral resistance, therefore it is a popular choice for application. However, some challenges need to be considered such as the phenomenon of buckling failure and a considerable increase in mass due to its self-weight. One way to overcome buckling failure is using a Buckling Restrained Base, while Lee (2015) utilized carbon fiber composite cables as bracing. Besides not having buckling failure and being lightweight, this bracing has an easy installation process which is also an interesting consideration. Through Lee's research, it was found that fiber cable bracing is effective in increasing the lateral resistance of a structure, but to implement it in SAP2000 for a wide variety of structures, a proper and validated cable bracing modeling procedure is needed to obtain realistic structural behavior. In the validation process, the cable is modelled with a frame element in the form of a solid pipe by modifying its elasticity, so that adjustments are obtained as follows: The elasticity is reduced by 35% from the elasticity of the initial specification material in the flat plate connection type, and 5% reduction for the protrusion connection. Moment and compressive release of course need to be enabled since these two conditions do not exist in cable bracing, while the initial and total axial forces can be obtained from modeling the bracing with cable elements. The cable element in SAP2000 can accommodate checking the initial and total stresses at the ultimate load. However, in the performance analysis, cable elements are not recommended and are replaced with validated frame elements.